Integration of pharmacist independent prescribers into general practice: a mixed-methods study of pharmacists' and patients' views - Abdullah A. Alshehri; Ali M. K. Hindi; Ejaz Cheema; M. Sayeed Haque; Zahraa Jalal; Asma Yahyouche (Taylor & Francis Group, 2023)
Abstract Background Since 2015, the National Health Service (NHS) has funded pharmacists to work in general practice (GP practice) to ease workload pressures. This requires pharmacists to work in new roles and be integrated effectively in GPs. Independent prescribing is a key part of the GP pharmacist role, but little is known about pharmacists' integration into GP practice as well as patients' perceptions and experiences of the care provided by GP pharmacists. This study aims to explore the perceptions of pharmacist independent prescribers (PIPs) about their integration into GP practice and gain insight into patients' perceptions about the care provided to them by pharmacists. Methods A mixed-methods study comprising semi-structured interviews with PIPs (n = 13) followed by questionnaire-based assessment of patients' (n = 77) evaluation of pharmacists' care was conducted between December 2019 and March 2020. Quantitative data were analysed using descriptive statistics. Interviews and open comments of the survey were thematically analysed. Results Pharmacist independent prescribers reported undertaking a range of patient-facing and non-clinical roles. Lack of understanding about PIPs' clinical role and working beyond their clinical area of competence were some of the barriers to their integration into GP practice. Most patients were satisfied with the consultations they received from pharmacists and reported confidence in the pharmacist's recommendations about their health conditions. However, a few patients (14%) felt they would still need to consult a general practitioner after their appointment and 11% were not sure if a further consultation was needed. Conclusions Pharmacist independent prescribers provide a range of clinical services for the management of long-term conditions which appear to be recognised by patients. However, there is a need to address the barriers to PIPs' integration into GP practice to optimise their skill-mix and patient-centred care.